The Role of Job Satisfaction as a Mediating Influence of Leadership and Organizational Climate on Employee Performance - Putra, Ida Bagus Bagus Udayana; Sutrisman, Melissa Percilla; Amertha, I Made Suniastha (Jurnal Ekonomi Kuantitatif Terapan; Vol 17 No 2 (2024): Vol. 17, No. 2, Agustus 2024 (pp.156-369)DO - 10.24843/JEKT.2024.v17.i02.p11, 2024)
This study aims to analyze the effect of leadership and organizational Climate on employee performance, with job satisfaction as an intervening variable. The object of this research is PT Restu Sandhika. The sample in this study was determined by the census method using all 87 employees as respondents. The data collection method is a survey method with a questionnaire. The analysis technique used is the inferential analysis technique with Partial Least Square (PLS). The results found that leadership does not directly affect employee performance but has a significant effect on job satisfaction. Meanwhile, organizational Climate has a significant positive effect on employee performance and job satisfaction. In addition, job satisfaction can mediate the relationship between leadership and employee performance but cannot mediate the relationship between organizational Climate and employee performance.